Pheromone-mediation of host-selection in bont ticks (Amblyomma hebraeum Koch) - Norval, R.A.I.; Andrew, H.R.; Yunker, C.E. (American Association for the Advancement of Science, 1989)
The bont tick, Amblyomma hebraeum, is the principal vector to southern African ruminants of heartwater (Cowdria ruminantium infection). The role of feeding male ticks, which emit an aggregation-attachment pheromone, in attracting unfed ticks to cattle was investigated. Calves infested with feeding male ticks were more attractive to unfed adult ticks than were uninfested calves. The presence of the pheromone on previously infested cattle apparently allows unfed ticks to discriminate between hosts on which these parasites have fed successfully (suitable hosts) and those on which they have not (potentially unsuitable hosts). The use of acaricides is thus unlikely to reduce bont tick populations in areas where adequate numbers of alternate (wild) hosts are present. Also, cattle so treated may lose their resistance to heartwater through lessened exposure to infected ticks.